2004
DOI: 10.1577/m03-025.1
|View full text |Cite
|
Sign up to set email alerts
|

Summer Movements within the Fish Community of a Small Montane Stream

Abstract: We studied movements by fishes in Chamberlain Creek, Montana, from 24 July to 16 August 2001. We operated six weirs with two‐way traps and one additional upstream trap, separated by 14–1,596 m, to quantify the timing, direction, and distance of movements and to estimate fish populations in the study reaches. We trapped and marked 567 fish of seven species, including 368 westslope cutthroat trout Oncorhynchus clarkii lewisi and 172 sculpin (slimy sculpin Cottus cognatus and an unidentified species similar to mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
47
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 38 publications
5
47
0
Order By: Relevance
“…Similar to the results of McCleave (1964), Potomac sculpin showed a preference for upstream movement, and this trend expanded with time. Similar to the Brown and Downhower (1982) and Schmetterling and Adams (2004) with freshwater sculpins, we found the length of Potomac sculpin did not affect movement. Several flood events occurred during our study, and we found, as did Anderson (1985), that floods did not increase movement rates.…”
Section: Discussionsupporting
confidence: 66%
See 3 more Smart Citations
“…Similar to the results of McCleave (1964), Potomac sculpin showed a preference for upstream movement, and this trend expanded with time. Similar to the Brown and Downhower (1982) and Schmetterling and Adams (2004) with freshwater sculpins, we found the length of Potomac sculpin did not affect movement. Several flood events occurred during our study, and we found, as did Anderson (1985), that floods did not increase movement rates.…”
Section: Discussionsupporting
confidence: 66%
“…The maximum distance moved was 1,711 m in 75 d. Only Natsumeda (1999) and Schmetterling and Adams (2004) found movement over 200 m (290 m and 209 m, respectively). These long-distance movers can be a key to recolonization of habitats lost to stochastic or anthropogenic events.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Movements in fall and winter, associated with declining water temperatures and ice formation, have been of similar magnitude Mackay 1995, Jakober andothers 1998). Moreover, mobility is common among cutthroat trout of all ages in small streams, and is not simply attributable to a few wandering individuals Fausch 2003a, Schmetterling andAdams 2004).…”
Section: Migratory Life History Typesmentioning
confidence: 99%